Extent of lymphovascular space invasion and risk of pelvic lymph node metastases in stage IB1 cervical cancer. - Chandacham A. (2014)
OBJECTIVE: To evaluate whether the extent of lymphovascular space invasion (LVSI) is a risk factor for pelvic lymph node metastases in stage IBI cervical cancer. MATERIAL AND METHOD: The clinicopathological data of 397 patients with stage IB1 cervical cancer undergoing radical hysterectomy and pelvic lymphadenectomy (RHPL) at Chiang Mai University Hospital between January 1998 and December 2002 were analyzed. The histology, tumor grade, depth of stromal invasion, uterine corpus involvement, parametrial invasion and LVSI were analyzed for their association with pelvic node metastases. The extent of LVSI was classified as negative, minimal (< 10 LVSI/cervical specimen), and extensive (> or = 10 LVSI/cervical specimen). RESULTS: Of the 397 patients, 146 (36.8%) had tumors containing LVSI, 82 (20.7%) and 64 (16.1%) had minimal and extensive LVSI, respectively. Fifty nine (14.9%) patients had pelvic node metastases. Using multivariable analysis, LVSI (p < 0.001), depth of stromal invasion (p < 0.001), tumor grade (p < 0.001), and parametrial invasion (p < 0.001) were significant predictors of pelvic node metastases. The extent of LVSI either minimal or extensive degree significantly influenced pelvic node metastases. CONCLUSION: The presence of LVSI especially extensive involvement was significantly associated with the risk of pelvic node metastases in stage IB1 cervical cancer.